A new triazine based π-conjugated mesoporous 2D covalent organic framework: its in vitro anticancer activities. Issue 81 (26th September 2018) - Kanti Das, Sabuj; Mishra, Snehasis; Manna, Krishnendu; Kayal, Utpal; Mahapatra, Supratim; Das Saha, Krishna; Dalapati, Sasanka; Das, G. P.; Mostafa, Amany A.; Bhaumik, Asim
Abstract : A new 2D π-conjugated COF, TrzCOF has been synthesized and it showed excellent anticancer activity for the colorectal carcinoma HCT-116 cell line. Abstract : We report a new highly crystalline 2D π-conjugated hexagonal mesoporous covalent organic framework material, TrzCOF, through the solvothermal polycondensation of 1, 3, 5-tri(4-formylbiphenyl) benzene [Ph7 (CHO)3, TFBPB] with 2, 4, 6-tris(4-aminophenyl)-1, 3, 5-triazine (TAPT) and it displayed excellent anticancer activity for human colorectal carcinoma HCT-116 cells.